Direct Renin Inhibition with Aliskiren Improves Ischemia-Induced Neovasculogenesis in Diabetic Animals via the SDF-1 Related Mechanism. - Ting-Ting Chang; Tao-Cheng Wu; Po-Hsun Huang; Chih-Pei Lin; Jia-Shiong Chen; Liang-Yu Lin; Shing-Jong Lin; Jaw-Wen Chen (PLoS ONE, 2015)
Aliskiren is a direct renin inhibitor which is suggested to modify proangiogenic cells in addition to lower blood pressure. Given that angiogenesis is impaired in the presence of diabetes mellitus, we would like to investigate whether and how aliskiren enhances endothelial progenitor cells (EPCs) and improves ischemic-induced neovasculogenesis by an effect independent of blood pressure reduction in diabetic animals.Streptozotocin-induced diabetic mice were administered with either aliskiren (5 or 25 mg/kg/day) using an osmotic pump or hydralazine (2 or 10 mg/kg/day) given in drinking water for two weeks prior to a hind-limb ischemia surgery. Laser Doppler imaging and flow cytometry were used to evaluate the degree of neovasculogenesis and the circulating levels of EPCs, respectively.In streptozotocin-induced diabetic mice, aliskiren enhanced the recovery of limb perfusion and capillary density, increased the number of circulating Sca-1+/Flk-1+ EPC-like cells, and elevated the levels of the plasma vascular endothelial growth factor (VEGF) and stromal cell-derived factor (SDF)-1α in a dose-dependent manner, whereas there were no such effects in hydralazine-treated mice. Intraperitoneal administration of anti-SDF-1 neutralizing monoclonal antibodies abolished the effects of aliskiren.Independent of the reduction of blood pressure, aliskiren enhanced ischemia-induced neovasculogenesis in a dose-dependent manner via VEGF/SDF-1α related mechanisms in diabetic mice.